‘Breaking the myth: Toledo Cathedral on the international stage’: Toledo Cathedral: Building Histories in Medieval Castile by Tom Nickson, University Park, Pensylvannia: The Pennsylvania University Press, 2015 - Matilde Mateo (Journal of Art Historiography, 2017)
This review analyzes the contribution of Tom Nickson´s study from the position given to Spain within European Gothic by the Anglophone historiography. It argues that Nickson´s book is a radical departure from previous historiography, which had condemned Toledo Cathedral, and all Spanish gothic monuments, because they were thought to be mere copies of European models. Nickson, however, convincingly argues that Toledo Cathedral is a monument as interesting as its canonical French and English counterparts. He does so by employing a holistic, integrated, and diachronic approach, with an impressive amount of information, much of it new, which addresses some of the latest concerns in the historiography of art, the humanities, and the social sciences, such as the creation of an identity through the creation of memories.